The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21037/apm-21-424
|View full text |Cite
|
Sign up to set email alerts
|

Levels of S100 calcium binding protein B (S100B), neuron-specific enolase (NSE), and cyclophilin A (CypA) in the serum of patients with severe craniocerebral injury and multiple injuries combined with delirium transferred from the ICU and their prognostic value

Abstract: Background:To analyze the levels of S100 calcium binding protein B (S100B), neuron-specific enolase (NSE), and cyclophilin A (CypA) in the serum of patients with severe craniocerebral injury combined with delirium and multiple injuries transferred from the intensive care unit (ICU), and their prognostic value. Methods:The data of 98 patients with severe craniocerebral injury combined with delirium and multiple injuries admitted to our hospital from January 2018 to May 2019 were retrospectively analyzed as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Promising biomarkers are S100 calcium binding protein B (S100B) which is expressed by astrocytes and not only reflects cell death, but also BBB integrity and permeability; neuron-specific enolase (NSE) an isoenzyme highly specific to neurons, a biomarker of hypoxic brain damage and a marker of poor outcome after cardiac arrest; and Tau protein which maintains microtubules stability in axons and relates to forms of cognitive-impairment 7 9 . There are, however, many gaps in the literature to fully understand how these molecules interact and how they are associated with delirium occurrence 10 , 11 . Specifically, data on S100B are conflicting, since some studies have shown that patients with delirium had a higher serum level of S100B, and other studies have shown no association between this protein and delirium or other adverse outcomes 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising biomarkers are S100 calcium binding protein B (S100B) which is expressed by astrocytes and not only reflects cell death, but also BBB integrity and permeability; neuron-specific enolase (NSE) an isoenzyme highly specific to neurons, a biomarker of hypoxic brain damage and a marker of poor outcome after cardiac arrest; and Tau protein which maintains microtubules stability in axons and relates to forms of cognitive-impairment 7 9 . There are, however, many gaps in the literature to fully understand how these molecules interact and how they are associated with delirium occurrence 10 , 11 . Specifically, data on S100B are conflicting, since some studies have shown that patients with delirium had a higher serum level of S100B, and other studies have shown no association between this protein and delirium or other adverse outcomes 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, data on S100B are conflicting, since some studies have shown that patients with delirium had a higher serum level of S100B, and other studies have shown no association between this protein and delirium or other adverse outcomes 10 . Furthermore, there are no studies evaluating the association between inflammatory and brain-related biomarkers with Emergency Department (ED) delirium 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…22,23 The amount of NSE present in the brain predicts quantifiable measures of brain damage, which lead to strokes, hemorrhage, seizures, etc. 24 Recently, reports have published sufficient data of COVID-19 positive patients showing the elevated level of NSE, signifying the role of NSE as a potential clinical biomarker for COVID-19 because it primarily targets human respiratory and neurological systems. 25,26 Although the detection of protein cancer biomarkers is advantageous, it also possesses certain shortcomings.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There are, however, many gaps in the literature to fully understand how these molecules interact and how they are associated with delirium occurrence. [10][11] Speci cally, data on biomarkers for delirium such as S100B are con icting. 10 Furthermore, there are no studies evaluating the association between in ammatory and brain-related biomarkers with Emergency Department (ED) delirium.…”
mentioning
confidence: 99%
“…10 Furthermore, there are no studies evaluating the association between in ammatory and brain-related biomarkers with Emergency Department (ED) delirium. [11][12] Our primary goal was to evaluate S100B levels and their association with delirium occurrence in acutely ill older adults within their rst 24 h of ED admission. We also aimed to evaluate the association between S100B, NSE, Tau and cytokine panel (IL-1B, IL-4, IL-10, TNF-α and IFN-γ) with delirium.…”
mentioning
confidence: 99%